Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd010561
|View full text |Cite
|
Sign up to set email alerts
|

Immune tolerance induction for treating inhibitors in people with congenital haemophilia A or B

Abstract: A B S T R A C T BackgroundThe occurrence of factor inhibitory antibodies, or inhibitors, is a significant complication in the care of individuals with congenital haemophilia A or B. Currently, immune tolerance induction is the only known intervention to successfully eradicate inhibitors. However, ideal dosing regimens, and the comparative safety and efficacy of different immune tolerance induction regimens have not yet been established. ObjectivesThe objective of this review was to assess the effects of immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Several regimens for ITI have been described, with different dosing schedules and combined therapies [50][51][52][53][54][55][56] ; the selection of an ITI regimen is usually considered on a case-by-case basis. 57 The International ITI study is the only randomised controlled trial to date to evaluate the efficacy of ITI in patients with severe HA and good risk features (historical inhibitor titres <200 BU and immediate pre-ITI titres <10 BU), comparing a low-dose daily FVIII regimen of 50 IU/kg three times weekly with a high-dose regimen of 200 IU/kg. 55 The study demonstrated an almost 70% overall success rate in achieving tolerance, with no statistically significant difference between the two arms.…”
Section: Immune Tolerance Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several regimens for ITI have been described, with different dosing schedules and combined therapies [50][51][52][53][54][55][56] ; the selection of an ITI regimen is usually considered on a case-by-case basis. 57 The International ITI study is the only randomised controlled trial to date to evaluate the efficacy of ITI in patients with severe HA and good risk features (historical inhibitor titres <200 BU and immediate pre-ITI titres <10 BU), comparing a low-dose daily FVIII regimen of 50 IU/kg three times weekly with a high-dose regimen of 200 IU/kg. 55 The study demonstrated an almost 70% overall success rate in achieving tolerance, with no statistically significant difference between the two arms.…”
Section: Immune Tolerance Inductionmentioning
confidence: 99%
“…After successful ITI, patients are able to resume factor replacement therapies for prophylaxis and acute bleeding. Several regimens for ITI have been described, with different dosing schedules and combined therapies 50–56 ; the selection of an ITI regimen is usually considered on a case‐by‐case basis 57 …”
Section: What Are Our Treatment Options?mentioning
confidence: 99%
“…Con el advenimiento de mejores técnicas en la producción de factores, los métodos de inactivación viral y el uso de biotecnología en su producción, las complicaciones infecciosas han disminuido y prácticamente desaparecido, si bien continúa existiendo un riesgo potencial por nuevos agentes infecciosos. Los pacientes con inhibidores de alta respuesta requieren de estrategias de tratamiento como la inducción de tolerancia inmune para intentar la erradicación del inhibidor, sin embargo, hasta en 10-15% de los casos no se consigue su erradicación (9,10). En los pacientes con inhibidores de alta respuesta, hay mayor dificultad para el control de los sangrados con agentes de puente, la tasa de control de los sangrados varía entre 70 y 90%.…”
Section: Introductionunclassified
“…Several reviews [18], [19] have supported this assertion, but we note that Earnshaw et al's protocol for secondary ("rescue") ITI includes the option of using concentrates containing Factor VIII complexed to von-Willebrand factor (VWF). A recent systematic review and meta-analysis [20] assessed the effect of VWF on inhibitor eradication in patients with severe haemophilia A but failed to demonstrate an association between product type and ITI outcome, although the heterogeneity observed by the authors among different studies might reflect differences in the response to different products. Thus, considering this background and also that the final results of the randomized controlled RESIST study [21], which could contribute to clarify this controversial issue, are still awaited, we concur with the most recent Cochrane Review on ITI [20] that "The choice of immune tolerance induction regimen should be considered individually for each case, until further research provides additional evidence".…”
mentioning
confidence: 99%